2024
DOI: 10.3390/app14020950
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fine-Layering of Tailings Dam on the Variation Pattern of Infiltration Lines

Wenze Geng,
Zhifei Song,
Cheng He
et al.

Abstract: The type of soil and its compactness significantly influence its permeability coefficient, which in turn affects the drainage difficulty of soil pore water and the distribution of the infiltration line. However, current tailings dam models typically consider only a single soil layer instead of taking into account the differences in soil types and compactness, resulting in a deviation between simulated results and actual conditions. To address this issue, this study proposes three models with a gradually increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The authors of [8][9][10][11][12] demonstrated that terrain morphology, meteorological conditions, the ecological environment, and slope deformation indicators are key factors that must be considered in landslide risk assessment. Terrain morphology is the basic condition for landslides and determines the stability and bearing capacity of slopes [13]. It mainly includes the aspect, slope, curvature, and elevation, which are interrelated and interact with each other.…”
Section: Basis and Selection Of Evaluation Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of [8][9][10][11][12] demonstrated that terrain morphology, meteorological conditions, the ecological environment, and slope deformation indicators are key factors that must be considered in landslide risk assessment. Terrain morphology is the basic condition for landslides and determines the stability and bearing capacity of slopes [13]. It mainly includes the aspect, slope, curvature, and elevation, which are interrelated and interact with each other.…”
Section: Basis and Selection Of Evaluation Indicatorsmentioning
confidence: 99%
“…Therefore, the weighted activation strength of each fuzzy rule is calculated as shown in Equation (13).…”
Section: Fuzzy-bls Risk Assessment Model Structurementioning
confidence: 99%